SOSIALISASI RUMAH TIDAK LAYAK HUNI (RTLH) PULAU MAITARA TIDORE - Haryati, Haryati; Muhammad, Asri A; Marasabessy, Firdawaty; Husen, Risalmi; Hi Sabatun, Adirahmadi (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTOne of the most pressing and rapidly growing social issues in Indonesia is poverty, which affects all regions across the country, including North Maluku. Poverty arises from social inequality, one of the indicators of which is the prevalence of RTLH. According to data from Statistics Indonesia (BPS) in 2023, the number of people living in poverty in North Maluku Province increased to 83.80 thousand, including those residing on Maitara Island, Tidore. One of the government's solutions to address this issue is the RTLH program, implemented by the Ministry of PUPR through the Directorate General of Housing. This program is guided by PUPR Ministerial Regulation No. 7/PRt/M/2018 and Regulation No. 7/2022. However, the program has not achieved its targets, and aid distribution has not been accurately directed to those most in need. To address these shortcomings and to enhance community involvement and knowledge regarding uninhabitable housing, socialization activities are essential. Based on data collected through questionnaires, these socialization efforts have proven effective, as there was a measurable increase in participants' understanding across all assessment criteria related to RTLH.Keywords: Poverty, RTLH, Socialization, Maitara, North MalukuABSTRAKPermasalahan sosial terbesar dan berkembang pesat di Indonesia adalah kemiskinan, yang berdampak pada seluruh daerah yang ada di Indonesia salah satunya Maluku Utara. Kemiskinan muncul karena adanya kesenjangan sosial yang ditandai dengan permasalahan sosial salah satunya memiliki RTLH. Berdasarkan data BPS tahun 2023 jumlah penduduk miskin khusus Provinsi Maluku Utara mengalami peningkatan menjadi 83,80 ribu jiwa termasuk di dalamnya Pulau Maitara Tidore. Salah satu solusi yang dilakukan Pemerintah dalam menangani hal tersebut adalah dengan adanya program RTLH melalui Kementerian PUPR Ditjen Perumahan, yang berpedoman pada Peraturan Menteri PUPR Nomor 7/PRt/M/2018 Tahun 2018 dan Peraturan Menteri PUPR Nomor 7 Tahun 2022. Pelaksanaan program ini belum berhasil secara target, penerima bantuan belum tepat sasaran dalam pelaksanaannya. Untuk mengatasi hal tersebut dan meningkatkan peran serta masyarakat serta pengetahuan terkait dengan RTLH maka diperlukan adanya kegiatan sosialisasi. Kegiatan sosialisasi ini berhasil berdasarkan data yang diperoleh dari kuesioner, yaitu terjadi peningkatan pengetahuan pada semua kriteria penilaian tentang RTLH.Kata Kunci: Kemiskinan, RTLH, Sosialisasi, Maitara, Maluku Utara